Bringing Gender in - Women and Corruption in China. - Wang, Qi; Min, Dongchao (Kvinder, Køn & Forskning, 2015)
This article deals with women and corruption in China. The aim is to bring gender in and to make good the lack of focus on gender in studies of corruption in China. The article outlines different forms of female involvement in corruption, introduces various theories of corruption, and elaborates on the relevance of these theories in explaining and understanding the role of gender in the case of corruption in China. The article also proposes a theory of chaotic capital/resource acquisition as a supplement and discusses the potential of this theory in accounting for the role of women in corruption, whether as government officials or as the mistresses and wives (family members) of corrupt male officials.